Comparación de las características textiles de las fibras de la llama ch´aku (lama glama) y la alpaca huacaya (vicugna pacos) del centro de investigación y desarrollo de camélidos sudamericanos - lachocc - Bernabé Soles, Patricia Evelyn (2015)
This work was conducted at the Center for research and development of camelids in Lachocc community, located in the district of Huancavelica province of Huancavelica, Department of Huancavelica; in the period between October and December 2014 to determine the comparison of the characteristics of textile fibers called Ch'aku (Lama glama) and Huacaya alpaca (Vicugnapacos). Were taken samples of 50 llamas and 50 alpacas randomly, which were analyzed. For the parameter to fiber diameter, the llamas had a mean of 22,45μm, in alpacas was 21,19μm. Statistically significant differences (p>0,05) was not calculated. For the parameter the coefficient of variation of fiber diameter, the llamas had a mean of 21,2; in alpacas was 20,17. Statistically significant differences (p>0,05) was not determined. For the parameter standard deviation of fiber diameter, the llamas had a mean of 4,78; in alpacas was 4,21. Statistically significant differences (p<0,05) was calculated. For the characteristic staple length, the llamas had an mean of 85 mm in alpacas was 120,5 mm. Highly significant statistical difference (p<0,01) was determined. For the parameter fineness for spinning, llamas had an average of 21,92μm in alpacas was 20,2μm. Statistically significant differences (p>0,05) was not calculated. For the parameter comfort index fiber, the llamas had a mean of 91,03%; in alpacas was 93,63%. Statistically significant differences (p>0,05) was not calculated. For the characteristic curvature index parameter, the llamas had a mean of 37,67grad/mm; in the alpacas was 34,85grad/mm. Statistically significant differences (p>0,05) was not determined. The llama fiber dehairing process after fiber flame ch'aku are similar except the standard deviation and staple length of huacaya alpaca.